FIrpic thin film as saturable absorber for passively Q-switched and mode-locked erbium-doped fiber laser - Salam, Sameer (Elsevier, 2019)
In this paper, we demonstrate the generation of passive all-fiber Q-switched and mode locked erbium doped fiber lasers (EDFLs) by using Bis[2-(4,6-difluorophenyl)pyridinato-C2,N](picolinato) iridium(III) (FIrpic) as a saturable absorber (SA). The material was prepared by solvent-casting technique and inserted between two fiber ferrules to form an SA. Then it was placed in an EDFL cavity. A stable Q-switched pulse laser operating at 1560.4 nm was achieved at a threshold pump power of 30 mW. The pulse repetition rate increased from 39.22 to 87.4 kHz and the pulse width decreased from 9.5 to 3.4 µs as the pump power was gradually increased from 30 to 208 mW. Meanwhile, a soliton self-starting mode-locking pulses at a wavelength of 1562.57 nm was achieved by adding an additional 52 m SMF to the EDFL cavity. The mode-locked laser had a repetition rate of 3.43 MHz and a pulse width of 120 ns within the pump power of 35–185 mW. The results suggest that FIrpic SA can be used to produce stable Q-switched and mode-locked fiber lasers at a low pump power. © 2019 Elsevier Inc.